2006
DOI: 10.1002/14651858.cd004762.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment for myotonia

Abstract: Due to insufficient good quality data and lack of randomised studies, it is impossible to determine whether drug treatment is safe and effective in the treatment of myotonia. Small single studies give an indication that clomipramine and imipramine have a short-term beneficial effect and that taurine has a long-term beneficial effect on myotonia. Larger, well-designed randomised controlled trials are needed to assess the efficacy and tolerability of drug treatment for myotonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 87 publications
2
25
0
4
Order By: Relevance
“…12 Our patients showed a dramatic response to carbamazepine treatment, resulting in abolition of life-threatening laryngeal spasms and marked improvement of the myotonia and muscle stiffness, corresponding to observations in recently reported cases with a similar genetic background. 13 Similar beneficial effects have been reported in response to drugs with a comparable mechanism of action, such as phenytoin and mexiletine.…”
Section: Discussionsupporting
confidence: 89%
“…12 Our patients showed a dramatic response to carbamazepine treatment, resulting in abolition of life-threatening laryngeal spasms and marked improvement of the myotonia and muscle stiffness, corresponding to observations in recently reported cases with a similar genetic background. 13 Similar beneficial effects have been reported in response to drugs with a comparable mechanism of action, such as phenytoin and mexiletine.…”
Section: Discussionsupporting
confidence: 89%
“…Single case reports have shown that mexiletine is effective in treating myotonia in both sodium and chloride channel disorders (Ceccarelli et al, 1992;Jackson et al, 1994). However, a recent Cochrane review highlighted the lack of adequate randomized double blind placebo controlled trials to prove efficacy (Trip et al, 2006). The ability to conduct such trials is partly hampered by the difficulty in quantitating myotonia (Torres et al, 1983;Hammaren et al, 2005;Logigian et al, 2005;Moxley et al, 2007;Hogrel, 2009) and in recruiting adequate numbers of patients to achieve statistical power.…”
Section: Treatmentmentioning
confidence: 99%
“…Moreover, a recent Cochrane review concluded that none of the myotonia treatment studies reported as of 2006 were of sufficiently high quality to conclude that any available drug treatment of myotonia is effective and safe. 26 Given the need for a more definitive antimyotonia treatment trial, we prospectively evaluated the effect of mexiletine on grip myotonia and cardiac conduction in DM1 in 2 randomized, double-blind, placebocontrolled crossover trials, the first using a dosage of 150 mg 3 times daily (TID) and the second using 200 mg TID. Patients were eligible if they were between the ages of 18 and 80, could walk 15 feet independently, had sufficient finger flexor strength to grasp a handle, met standard clinical criteria for the presence of myotonia (time for fingers to fully uncurl following maximal hand grip estimated by visual inspection to be 3 seconds or more, or percussion myotonia in wrist extensor and thenar muscles), satisfied clinical criteria for DM1, 27 and had genetic confirmation of the diagnosis.…”
mentioning
confidence: 99%